UiTM amateur satellite ground station: installation and performance / S. N. Mohamad Rahim … [et al.] - Mohamad Rahim, S. N.; Azami, M. H.; Hamidi, Z. S.; Ab Rahim, S. A. Enche; Jusoh, M. H. (Universiti Teknologi MARA, 2019)
This paper describes the installation of UiTM's Ground Station. UiTM’s ground station is a part of BIRDS Ground Station Networks, established to support BIRDS-2 nanosatellite's monitoring. The ground station has been installed with two (2) Yagi antennas which operate in Amateur bands respectively at very-high-frequency (VHF) at 144 MHz - 148 MHz ranges and ultra-high-frequency (UHF) at 430 MHz - 438 MHz ranges. Additionally, a KX-137 antenna, which functions as the APT receiving system also has been installed. As a precaution, a Radio Frequency Interference (RFI) testing was conducted at the perimeter of the ground station to identify the interference sources available within the range of 1 – 2000 MHz. The installation completed and tested with several satellites to ensure the functionality of the station system (amateur radio frequency satellite for Yagi antenna and NOAA satellite for KX-137 antenna). As a result, the hardware and software the ground station system are confirmed to be working as expected with the successful reception of satellite signal from NOAA, UiTMSAT-1 and other satellites.